Conceptual foundations of entrepreneurial strategy: A systematic literature review - Branco, Lídia (2021)
Objective: The objective of the article is to contribute to a greater and deeper understanding of the ES conceptualisation. The relevance of the topic of Entrepreneurial Strategy (ES) stems from growing interest of society in entrepreneurship, which has become extensively discussed although the concept of ES is still poorly understood.